Íñigo Errejón, Chantal Mouffe (2015), Construir Pueblo. Hegemonía y radicalización de la democracia, Barcelona: Icaria Editorial - Fittipaldi, Raffaella (PARTECIPAZIONE E CONFLITTO, 2017)
For Book Reviews abstract is not required